Feline urethral plugs and bladder uroliths: A review of 5484 submissions 1998–2003 - Houston, Doreen M. (Canadian Veterinary Medical Association, 2003)
The results of 5484 submissions from cats to the Canadian Veterinary Urolith Centre between February 1998 and February 2003 are presented. Of the submissions, 618 were urethral plugs and 4866 were bladder uroliths. The majority of the urethral plugs were from male domestic shorthair and longhair cats. Approximately 50% of the urolith submissions were oxalate, 44% were struvite. Oxalate uroliths were the most common mineral type in males and in Himalayan, Persian, and Siamese cats. Struvite uroliths were the most common mineral type in domestic shorthair and longhair cats. Females outnumbered males by 1.4:1 in struvite urolith submissions. A review of risk factors for urethral plugs and bladder uroliths is presented.